ANALYSIS OF FACTORS DETERMINING THE LEVEL OF LIQUIDITY RISK IN COMMERCIAL BANKS - Yormatov Ilmidin Toshmatovich; Kodirov Azamatjon Bakhodirovich (Scholars Digest Publishing, 2024)
The article presents research aimed at identifying the key factors influencing liquidity risk levels in commercial banks' operations. The authors analyze various aspects such as the bank's asset and liability structure, credit risk level, liquidity management efficiency, external economic conditions, and other factors that may impact a bank's liquidity. The article also examines modern approaches to liquidity risk management and offers recommendations for reducing risk levels and enhancing the financial stability of commercial banks. This article may be beneficial for professionals in finance, banking, and risk management, as well as researchers and students interested in liquidity issues in the banking sector.
Keywords: liquidity, commercial banks, risk management, assets and liabilities, credit risk, financial stability, economic conditions, liquidity level, risk factors.